IbM KELOMPOK ORGANISASI MAHASISWA UNIVERSITAS LANCANG KUNING DALAM PENGGUNAAN SOFTWARE DESIGN GRAFIS - Monice; Perinov (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
Nowadays, in the younger generation, students in particular, there is less and less motivation for entrepreneurship. This is also because many do not have the skills that can be used to support it. Student organizations are a representative of a part of younger generation who have problems of their own. Student organizations have many activities, which requires skill and expertise in the field of graphic design. This activity, Science and Technology for Community is a positive step to expand the horizons and motivate the younger generation, especially students through student organizations in order to foster an entrepreneurial spirit and the spirit to always learn new things and keep up with technology. The targets of this Science and Technology for Community activity are students who represent their Student Organizations in Lancang Kuning University will have skill in using graphic design software, namely Adobe Indesign, and insight into the magnitude of the business opportunities in the field of graphic design which can help the Student Organization’s activities. The methods which are used, such as workshop or training in using graphic design software and discussion to open up horizons for entrepreneurship. Material which is provided, include handout of Basic Training for Adobe Indesign for making posters, brochures and banners, as well as ideas of business opportunities that can be developed by students or student organizations. Conclusions, outcomes achieved are the participants have basic skills and knowledge in using the software Adobe Indesign for making posters, and the emergence of ideas in entrepreneurship in the field of graphic design from the participants.